Bioimpedance Spectroscopy for Assessment of Breast Cancer-Related Lymphedema: A Systematic Review. Issue 2 (April 2020) - Forte, Antonio J.; Huayllani, Maria T.; Boczar, Daniel; Ciudad, Pedro; Lu, Xiaona; Kassis, Salam; Parker, Alexander S.; Moore, Pamela A.; McLaughlin, Sarah A.
Abstract : Bioimpedance spectroscopy is currently used to evaluate patients with breast cancer-related lymphedema (BCRL). We aimed to describe published studies on the use of bioimpedance spectroscopy for assessment for BCRL. We queried the PubMed, Ovid Medline, and Embase databases to identify studies that evaluated the use of bioimpedance spectroscopy as an assessment tool. We searched for the keywords "bioimpedance" AND ("lymphedema" OR "lymphoedema"). We included English-language studies that reported the use of bioimpedance spectroscopy for assessment of BCRL. Out of 152, 116, and 235 articles identified in each database, respectively, only a total of 11 articles were included. Bioimpedance spectroscopy was studied as a method to assess and predict response to BCRL treatment, assess volume changes, and calibrate L-Dex scores for conversion to units of volume. All studies reported that bioimpedance spectroscopy is a promising tool for predicting response to BCRL treatment and measuring volume changes. Bioimpedance spectroscopy can be used for assessment of BCRL. However, the accuracy of bioimpedance spectroscopy for BCRL assessment has not been determined, and consequently further studies are needed.